STATUS MUTU KUALITAS AIR SUNGAI GARANG HILIR KAITANNYA DENGAN PERUBAHAN PENGGUNAAN LAHAN DI SUB DAS GARANG HILIR SEMARANG (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2017)
Changes in land use that occur in the watershed indicate a decrease in water quality one of them in the Garang Hilir Sub watershed . Land use in watershed has a great impact on river water quality. Changes in land cover and land management practices have been considered key factors affecting changes in hydrological systems, leading to changes in runoff and water quality. The objectives of the study were to assess changes in land use, changes in water quality and the linkages between them. The analysis used is land use change and calculation of Water Quality Index-Garang Hilir River (IKA-SGH). Determination of Water Quality Index of Garang Hilir River (IKA-SGH) using objective analytical approach secondary data of water quality of measurement from Environmental Agency (BLH) of Central Java Province from September 2002 to June 2014 in 4 (four) monitoring sites in Garang River. Water quality index is done in three stages namely the selection of dominant parameters with the help of Factor Analysis, the weighting of dominant parameters with Analytical Hierarchy Process (AHP) approach is Pairwise comparison and making sub-index graph. The effect of land use change on water quality using quantitative descriptive analysis. The data used to determine the relationship is the average value of the Garang River Water Quality Index (IKA-SGH) and the extent of land use change from 2002 to 2014. In general the quality status of water quality in Garang Hilir River from 2002 to 2014 is in the